2010
DOI: 10.1080/1745039x.2010.496952
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotides in canine colostrum and milk at different stages of lactation

Abstract: The aim of this study was to investigate the presence of nucleotides in canine colostrum and milk during lactation. Colostrum and milk samples of 10 healthy bitches were collected manually from mammary glands and analysed for total milk solids, crude protein and adenosine 5'-monophosphate (AMP), cytidine 5'-monophosphate (CMP), guanosine 5'-monophosphate (GMP) and uridine 5'-monophosphate (UMP). We found that the total nucleotide content significantly (p < 0.05) increased during lactation, with UMP and CMP bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Segarra et al [12] demonstrated that nucleotides improve biological markers of immune response in dogs and helped to a better-health status. This is particularly true for puppies since all tissues are in rapid growth and moreover the immune system is still incomplete [1011]. The best way to achieve a dietary integration of nucleotides is to add them directly to a commercial food, even if the main source of these elements for healthy subjects is usually represented by meat and its by-product, which represent one of the main components of their maintenance diet.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Segarra et al [12] demonstrated that nucleotides improve biological markers of immune response in dogs and helped to a better-health status. This is particularly true for puppies since all tissues are in rapid growth and moreover the immune system is still incomplete [1011]. The best way to achieve a dietary integration of nucleotides is to add them directly to a commercial food, even if the main source of these elements for healthy subjects is usually represented by meat and its by-product, which represent one of the main components of their maintenance diet.…”
Section: Resultsmentioning
confidence: 99%
“…So far, different studies on nucletotides supplementation are available in farm animals, while few studies had been conducted in pets. Rutherfurd-Markvick et al [9], demonstrated that 43 cats fed with an integrated diet with nucleotides showed an increased proliferative response of post-vaccination lymphocytes while other authors showed an improvement of the immune system in puppies fed with supplemented food [1011] or in dogs suffering from leishmaniasis [12]. Given the above and in the view of a commercial growing trend of nucleotides supplementation also in pets, it is important to properly understand if and how nucleotides can undergo alterations during pet food processing and storage.…”
Section: Introductionmentioning
confidence: 99%
“…The nutrient profiles (protein, lipids, and carbohydrate content) of canine milk differ from those of other mammals [7]. Some active components in canine milk, including oligosaccharides (3 -sialyllactose, 6 -sialyllactose, and 2 -fucosyllactose), nucleotides (adenosine 5 -monophosphate, cytidine 5 -monophosphate, guanosine 5 -monophosphate, and uridine 5 -monophosphate), and immunoglobulin G were significantly different from other mammals [2,8,9]. However, the protein profile, fatty acid composition, and mineral content of canine milk are seldom reported.…”
Section: Introductionmentioning
confidence: 84%
“…Increasing numbers of families raise dogs as partners and care for their health and growth. Breast milk is an essential source of nutrients (proteins, lipids, carbohydrates, vitamins, and minerals) for newborn puppies [1,2]. The bioactive composition of breast milk can regulate the development of the intestinal tract and immune system via its antimicrobial and anti-inflammatory effects [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…), have been extensively studied, and their roles in cellular maintenance and propagation, lipid metabolism and hepatic function have been comprehensively investigated in recent years. 42 UMP was the predominant nucleotide analogue found in sow milk, 43 probably as a response to a specific need of the piglets. In the present study, maternal UR supplementation decreased the V/C ratio in the jejunum of neonatal piglets and in the duodenum of suckling piglets.…”
Section: Discussionmentioning
confidence: 99%